ATRT-28. RETROSPECTIVE ANALYSIS OF ATYPICAL TERATOID RHABDOID TUMOR IN THE ERA OF MULTIMODAL TREATMENT IN JAPAN. Issue 2 (22nd June 2018) - Yamasaki, Kai; Watanabe, Yuko; Isobe, Kiyotaka; Koga, Yuhki; Kiyotani, Chikako; Terashima, Keita; Arakawa, Yoshiki; Hasegawa, Daiichiro; Kosaka, Yoshiyuki; Goto, Hiroaki; Koh, Katsuyoshi; Hara, Junichi
Abstract: BACKGROUND: Recent progress of multimodal therapy including intrathecal and/or intraventricular chemotherapy improved the prognosis of atypical teratoid rhabdoid tumor (ATRT). To know historical control data for a new trial, we retrospectively collected clinical information of locally diagnosed ATRT in eight major pediatric cancer centers in Japan. RESULT: From 2005 to 2016, 38 ATRT cases with INI-1 immunostaining negative were enrolled in this analysis. Median age was 1.3 years (2m to 11.8yr) and male to female ratio was 2:1. More than half of patients were positive for metastases (M1: 6, M2: 7, M3: 7, M4: 2). Four patients died of cerebral herniation or intratumoral hemorrhage before the initiation of chemotherapy. Postoperative chemotherapy was performed in all remaining patients. Intrathecal methotrexate was added in 30/34 (88.2%) cases. Most patients received high-dose chemotherapy (n=8), radiotherapy (n=9) or both (n=13). By a median follow up of 40.9 month, the 3-year progression free survival (PFS) and overall survival (OS) in treated patients were 39.1 ± 8.7% and 58.5 ± 9.1%, respectively. 3yr-PFS was 56.0 ± 11.8% for M0-1 and 21.4 ± 11.0% for M2-3 cases (p=0.0427) and 76.2 ± 14.8% for GTR and 25.8 ± 9.2% for non GTR (p=0.0361). Neither HDC nor radiotherapy was prognostic, however, all three patients treated with chemotherapy alone relapsed (n=3). Notably, three patients with late relapse survived long periods after relapse (40m, 46m, 80m). CONCLUSION: A comparable result as previous reports was shown in Japan. We are currently planning a new clinical trial for ATRT.